Emergence of CD4+ and CD8+ Polyfunctional T Cell Responses Against Immunodominant Lytic and Latent EBV Antigens in Children With Primary EBV Infection - Lam, Janice K. P.; Hui, K. F.; Ning, Raymond J.; Xu, X. Q.; Chan, K. H.; Chiang, Alan K. S. (Frontiers in Microbiology, 2018)
Long term carriers were shown to generate robust polyfunctional T cell (PFC) responses against lytic and latent antigens of Epstein-Barr virus (EBV). However, the time of emergence of PFC responses against EBV antigens, pattern of immunodominance and difference between CD4+ and CD8+ T cell responses during various stages of EBV infection are not clearly understood. A longitudinal study was performed to assess the development of antigen-specific PFC responses in children diagnosed to have primary symptomatic (infectious mononucleosis [IM]) and asymptomatic (AS) EBV infection. Evaluation of IFN-γ secreting CD8+ T cell responses upon stimulation by HLA class I-specific peptides of EBV lytic and latent proteins by ELISPOT assay followed by assessment of CD4+ and CD8+ PFC responses upon stimulation by a panel of overlapping EBV peptides for co-expression of IFN-γ, TNF-α, IL-2, perforin and CD107a by flow cytometry were performed. Cytotoxicity of T cells against autologous lymphoblastoid cell lines (LCLs) as well as EBV loads in PBMC and plasma were also determined. Both IM and AS patients had elevated PBMC and plasma viral loads which declined steadily during a 12-month period from the time of diagnosis whilst decrease in the magnitude of CD8+ T cell responses towards EBV lytic peptides in contrast to increase towards latent peptides was shown with no significant difference between those of IM and AS patients. Both lytic and latent antigen-specific CD4+ and CD8+ T cells demonstrated polyfunctionality (defined as greater or equal to three functions) concurrent with enhanced cytotoxicity against autologous LCLs and steady decrease in plasma and PBMC viral loads over time. Immunodominant peptides derived from BZLF1, BRLF1, BMLF1 and EBNA3A-C proteins induced the highest proportion of CD8+ as well as CD4+ PFC responses. Diverse functional subtypes of both CD4+ and CD8+ PFCs were shown to emerge at 6 to 12 months. In conclusion, EBV antigen-specific CD4+ and CD8+ PFC responses emerge during the first year of primary EBV infection, with greatest responses towards immunodominant epitopes in both lytic and latent proteins, correlating to steady decline in PBMC and plasma viral loads.